2018
DOI: 10.1139/gen-2017-0164
|View full text |Cite
|
Sign up to set email alerts
|

Longissimus dorsi muscle transcriptomic analysis of Yunling and Chinese simmental cattle differing in intramuscular fat content and fatty acid composition

Abstract: Intramuscular fat (IMF) content and fatty acid (FA) composition vary significantly across beef cattle breeds, which play an important role in taste and nutritional value. However, the molecular mechanisms underlying these phenotypic differences remain unknown. The present study compared meat quality traits between Yunling cattle and Chinese Simmental cattle. Yunling cattle showed a lower IMF content and proportion of monounsaturated fatty acids (MUFA), as well as higher proportions of saturated fatty acids (SF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
23
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 60 publications
3
23
1
1
Order By: Relevance
“…This mechanism may be important for growth, lean mass and FE. The glucagon signalling pathway was identified as a significant overrepresented pathway for intramuscular fat content and fatty acid composition in Longissimus dorsi muscle of Simmental and Yunling cattle (Zhang et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism may be important for growth, lean mass and FE. The glucagon signalling pathway was identified as a significant overrepresented pathway for intramuscular fat content and fatty acid composition in Longissimus dorsi muscle of Simmental and Yunling cattle (Zhang et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…They belong to the unique breed of milk and meat in Northeast China, and have a good quality, a high content of protein in beef and unsaturated fatty acids, especially the linoleic acid and conjugated linoleic acid, and a delicious flavour that is very suitable for the oriental taste. The quality of the beef is not only affected by the nutritional factors but also restricted by the genetic ones [28]. Therefore, it is of great significance to analyse the genetic factors affecting the beef quality at the molecular level to improve the beef quality and meat quality breeding.…”
Section: Discussionmentioning
confidence: 99%
“…The studies in the mouse 3T3-L1 cells showed that the interference with the Acot2 gene significantly inhibited the lipid accumulation and triglyceride content in the 3T3-L1 cells [27]. Based on the transcript analysis of the longissimus dorsi muscle and the differentially expressed genes of the intramuscular fat content and fatty acid composition between the Yunling cattle and Chinese Simmental cattle, the expression of the Acot2 gene was found to be upregulated in the Yunling cattle [28]. The expression of the Acot2 gene was also upregulated in the amiodarone-induced mouse model of the drug-induced fatty liver [32].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the significant GO terms identified, we highlighted the glycolytic process (GO:0006096), ATP binding (GO:0005524) and bone development (GO:0060348). The glycolysis encompasses chemical reactions and pathways resulting in the breakdown of carbohydrate into pyruvate, with the production of ATP and NAD(P)H. Pyruvate may be converted into small molecules, such as acetyl‐coenzyme A. Glycolysis influences the synthesis of cholesterol and FA (Siperstein & Fagan, 1958; Zhang et al., 2018). The bone development (GO:0060348) is a biological process related to the progression of bone over time, from its formation to the mature structure.…”
Section: Discussionmentioning
confidence: 99%